PREPARING FOR SUCCESS INSIGHTS FROM THE MUET BRIEFING SESSION - Siti Norzaimalina, Abd Majid; Siti Ainun Jariyah, Hassan (Pusat Bahasa Moden (PBM), 2024)
26 April 2024 – A briefing session for candidates of the Malaysia University English Test (MUET) was conducted via Microsoft Teams on 26 April 2024 at 10.00 am. The session was organised by the Competency Unit of the Centre for Modern Languages (CML) and led by Ms. Siti Ainun Jariyah Hassan, the Coordinator for MUET at the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Pekan campus. Its purpose was to prepare students with important information for examinations, which were scheduled for the following day.